Crosstalk‐Free Mesa‐Etched Passive‐Matrix Microscale Light‐Emitting Diode Array Using Yttrium‐Iron Garnet P‐Type Resistive‐Switching Electrodes (Advanced Optical Materials 3/2023). Issue 3 (3rd February 2023) - Kim, Jun Young; Lee, Ho Jin; Son, Kyung Rock; Yu, Min Ji; Hong, Seok Hee; Kim, Tae Geun
Abstract : Conventional passive‐matrix microscale light‐emitting diode (PM‐μLED) arrays suffer from electrical crosstalk between adjacent pixels. In article number 2202160, Tae Geun Kim and co‐workers demonstrate crosstalk‐free PM‐μLED arrays using yttrium iron garnet‐based p‐type resistive‐switching (RS) electrodes with high on/off ratio (>10 6 ) and good retention (10 5 s). On/off switching of the μLED pixels is realized through precise control of conductive paths in the RS layers by generating and annihilating oxygen vacancies. This work provides insights for implementing a compact driving circuit by removing the space required for pixel isolation.